This is Texas - Sasek, M. (Miroslav), 1916-1980 (Universe Publishing, 2006)
Texas, home state of three presidents, is also famed for its cattle, Cadillacs, coyotes and cowboys, oil wells and millionaires., Spanish missions and state fairs, rodeos and rattlesnakes. Everything in the biggest state is bigger than anywhere else. If you don't believe it, just ask any Texan, who will tell you taller tales than anyone else.